Product Design Innovation Based on Privet’s Customer Preferences - Krisnayanti Aditasari; Rahmatsyam Lakoro; Reny Nadlifatin; Jian Karisawati (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The footwear industry in Indonesia grew along with Indonesia's economic development that occurred in the early 1980s. The development of the footwear industry is also supported by the role of the government with various facilities provided to MSMEs. The local brand is currently growing, one of which is women's footwear products. Product consistency and innovation are important factors in enlarging the brand in the local and international markets. Privet is a business that manufactures women's footwear since 2018. This business was born in a class New Venture Creation at Business Management ITS. The problem of product innovation at Privet is how to produce products based on customer preferences. This research uses the five stages of the design thinking model proposed by the Hasso-Plattner Design Institute at Stanford, namely empathize, define, ideate, prototype, and test. Tests were carried out using the Capture Matrix and Net Promoter Score (NPS). From this research, it was found that the factors of customer preference in buying footwear are comfort, design, and product value. Therefore, it is recommended to create products innovation in shoes, slippers, and sandals category based on customer.